A proxemia e o fazer bibliotecário - Lunardelli, Rosane S. Alvares (2005)
Based on Hall’s theory of proxemics, the objective of this work is to provide some deeper reflections concerning the spatial behavior established among users and librarians at the library’s Reference Sector. Under the light of this theory, it is understood that studies about the pleasant and also the unpleasant states created by the organization and by the spatial distribution of people and objects, contribute effectively to turn the library into a pleasant area for knowledge mediation.